Regional cooperation in the South Caucasus good neighbours or distant relatives? - German, Tracey C. 1971- (Routledge Ashgate, 2012)
In this book, German explores the extent of regional cooperation in the South Caucasus, analyses the reasons for the relative lack of regional cooperation and assesses the potential for deeper cooperation in the future.